2020
DOI: 10.35787/jimdc.v9i1.386
|View full text |Cite
|
Sign up to set email alerts
|

Disease Pattern and Outcome among Neonates in Pediatric Ward of POF Hospital, Wah

Abstract: Background: Neonatal period is the duration between 0-28 days of birth and it is the most susceptible period of life because of the large number of problems and diseases which a neonate is likely to face. The objective of the study was to determine the disease pattern and outcome among neonates in Pediatric ward of POF Hospital.Material and Methods: A descriptive study was carried out at Pediatric ward of POF Hospital Wah Cantt. Retrospective data regarding age, sex, reasons for admission, outcome and mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…While the students perception of teachers’ knowledge was excellent and was rated as one of the highest scoring DREEM items in this institution, their feedback skills was the only item that scored less than 2 in this subscale. A similar area of concern has been noted in medical schools in UK, India, and Pakistan ( Dunne, McAleer and Roff, 2006 ; Kohli and Dhaliwal, 2013 ; Mushtaq et al, 2017 ). The negative response to this item may reflect inappropriate feedback methods rather than a total absence.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…While the students perception of teachers’ knowledge was excellent and was rated as one of the highest scoring DREEM items in this institution, their feedback skills was the only item that scored less than 2 in this subscale. A similar area of concern has been noted in medical schools in UK, India, and Pakistan ( Dunne, McAleer and Roff, 2006 ; Kohli and Dhaliwal, 2013 ; Mushtaq et al, 2017 ). The negative response to this item may reflect inappropriate feedback methods rather than a total absence.…”
Section: Discussionsupporting
confidence: 56%
“…This improvement can provide incentives for continuous betterment of the social conditions in the faculty. Globally, a number of studies reported similar findings in this subscale ( Bhosale, 2015 ; Mushtaq et al, 2017 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation